Comparative effectiveness of photobiomodulation and manual therapy alone or combined in TMD patients: a randomized clinical trial - Fernanda Thomé BROCHADO; Luciano Henrique de JESUS; Vinicius Coelho CARRARD; Angelo Luiz FREDDO; Karen Dantur CHAVES; Manoela Domingues MARTINS (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The effectiveness of photobiomodulation (PBM) and manual therapy (MT), alone or combined (CT), were evaluated in pain intensity, mandibular movements, psychosocial aspects, and anxiety symptoms of temporomandibular disorder (TMD) patients. Fifty-one TMD patients were randomly assigned to three groups: the PBM group (n = 18), which received PBM with 808 nm, 100 mW, 13.3 J/cm2, and 4 J per point; the MT group (n=16) for 21 minutes each session on masticatory muscles and temporomandibular joint TMJ; and the CT group (n = 17), applied during twelve sessions. Seven evaluations were performed in different moments using visual analogue scale (VAS), Research Diagnosis Criteria for Temporomandibular Disorders (RDC/TMD) Axis I and II, and Beck anxiety inventory (BAI). All groups demonstrated reductions in pain and improvement in jaw movements during treatment and at follow-up (< 0.001). The assessment of psychosocial aspects of TMD, comparing baseline and follow-up in all treatment groups, revealed that treatment did not promote modification in the intensity of chronic pain (p > 0.05). However, depression symptoms showed a reduction in PBM and CT groups (p≤0.05). All treatments promoted reduction in physical symptoms with and without pain and enhancement of jaw disabilities (p ≤ 0.05). MT promotes improvement in 5 functions, PBM in 2, and CT in 1 (p < 0.001). BAI analysis revealed that all treatments lead to a reduction in anxiety symptoms (p≤0.05). All protocols tested were able to promote pain relief, improve mandibular function, and reduce the negative psychosocial aspects and levels of anxiety in TMD patients. However, the combination of PBM and MT did not promote an increase in the effectiveness of both therapies alone.